Induction of Labour In Growth Restricted and Small for Gestational Age Fetuses - A Historical Cohort Study - Kehl, Sven; Weiss, Christel; Dammer, Ulf; Berlit, Sebastian; Grosse-Steffen, Thomas; Faschingbauer, Florian; Suetterlin, Marc; Beckmann, Matthias; Schneider, Michael (Zeitschrift für Geburtshilfe und Neonatologie, 2019)
Purpose Induction of labour for small-for-gestational-age (SGA) foetus or intrauterine growth restriction (IUGR) is common, but data are limited. The aim of this trial was therefore to compare labour induction for SGA/IUGR with cases with normal fetal growth beyond the 10th percentile.
CRIS-Team WoS Importer:2019-03-15